ARTIFICIAL INTELLIGENCE IN MODERN EDUCATION: OPPORTUNITIES, CHALLENGES AND STRATEGIC DIRECTIONS (Web of Technology: Multidimensional Research Journal, 2026)
The rapid development of artificial intelligence (AI) technologies has significantly influenced various sectors, including education. This paper examines the role of AI in modern educational systems, focusing on its potential to enhance learning processes through personalization, automation, and accessibility. At the same time, the study highlights critical challenges such as academic integrity risks, over-reliance on AI tools, and ethical concerns related to data usage. The paper argues that AI should be integrated as a complementary instrument rather than a replacement for human educators. Strategic directions for the effective and responsible implementation of AI in education are also discussed.